A main event and multiple introductions of SARS‐CoV‐2 initiated the COVID‐19 epidemic in Greece. Issue 5 (23rd February 2021) - Spanakis, Nikolaos; Kassela, Katerina; Dovrolis, Nikolas; Bampali, Maria; Gatzidou, Elisavet; Kafasi, Athanasia; Froukala, Elisavet; Stavropoulou, Anastasia; Lilakos, Konstantinos; Veletza, Stavroula; Tsiodras, Sotirios; Tsakris, Athanasios; et al.
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is a novel coronavirus responsible for the coronavirus disease 2019 (COVID‐19) pandemic. Chains of infections starting from various countries worldwide seeded the outbreak of COVID‐19 in Athens, capital city of Greece. A full‐genome analysis of isolates from Athens' hospitals and other healthcare providers revealed the variety of SARS‐CoV‐2 that initiated the pandemic before lockdown and passenger flight restrictions. A dominant variant, encompassing the G614D amino acid substitution, spread through a major virus dispersal event, and sporadic introductions of rare variants characterized the local initiation of the epidemic. Mutations within the genome highlighted the genetic drift of the virus as rare variants emerged. An important variant contained a premature stop codon in orf7a leading to the truncation of a possibly important for viral pathogenesis domain. This study may serve as a reference for resolving future lines of infection in the area, especially after resumption of passenger flight connections to Athens and Greece during summer of 2020. Highlights: COVID‐19 epidemic in Athens, Greece was mainly initiated by a major virus dispersal event. The dominant variant of SARS‐CoV‐2 at the beginning of COVID‐19 epidemic in Athens, Greece was G614D. A rare SARS‐CoV‐2 variant in Greece contained a premature stop codon in orf7a leading to the truncation of the protein.